A. E. Nordenskiöld in Swedish memory: the origin and uses of Arctic heroism. (3rd July 2019) - Wråkberg, Urban
ABSTRACT: For Nordic nations scientific activities in the Polar Regions proved significant in defining national identities and shaping scientific profiles. Starting in the nineteenth century and continuing throughout the next century, polar research proved instrumental in inculcating national honour and expressing small-state colonial aspirations. It provided a source of heroes for forging collective memory and the fostering of youth by presenting the polar explorer as a model character. This study explores the ideological lineage of the nineteenth century polar hero by first relating this idol to historical archetypes of Western culture. It identifies the special traits of the Nordic polar hero and discusses how it was used for patriotic purposes. As a case in point the article looks at the career of the Finnish-Swedish mineralogist and Arctic expedition leader Adolf Erik Nordenskiöld and the ways he, with the help of others, successfully navigated not only the drift ice of polar seas but also the international republic of science, and the three national scenes of Sweden, Finland and Russia. In the process he was turned into a national hero both in Finland and Sweden, and presented as a patriotic role model for adolescents in the arts of postponing gratification and enduring hardship.